2004
DOI: 10.1590/s0074-02762004000900020
|View full text |Cite
|
Sign up to set email alerts
|

Biomphalaria tenagophila/Schistosoma mansoni interaction: premises for a new approach to biological control of schistosomiasis

Abstract: Biomphalaria tenagophila is very important for schistosomiasis transmission in Brazil. However its mechanisms of interaction with Schistosoma mansoni are still scantly studied. Since this snail displays strains highly susceptible or completely resistant to the parasite infection, the knowledge of that would be a useful tool to understand the mechanism of snail resistance. Particularly, the Taim strain consistently shows absolute resistance against the trematode, and this resistance is a dominant character.A mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 17 publications
(8 reference statements)
0
19
0
Order By: Relevance
“…Therefore, the significant variation on labelling pattern by lectin observed among different species and strains of Biomphalaria used in this study could help to explain hemocyte binding around the parasite observed in some snail strain and, therefore it would be an important factor for determination of differences in the susceptibility level to S. mansoni infection reported in the snail species , Martins-Souza et al 2003, Coelho et al 2004, Pereira 2005, Rosa et al 2005.…”
Section: Discussionmentioning
confidence: 72%
“…Therefore, the significant variation on labelling pattern by lectin observed among different species and strains of Biomphalaria used in this study could help to explain hemocyte binding around the parasite observed in some snail strain and, therefore it would be an important factor for determination of differences in the susceptibility level to S. mansoni infection reported in the snail species , Martins-Souza et al 2003, Coelho et al 2004, Pereira 2005, Rosa et al 2005.…”
Section: Discussionmentioning
confidence: 72%
“…tenagophila Taim, from the Ecological Station of Taim, state of Rio Grande do Sul, Brazil, proved to be systematically resistant to S. mansoni. This resistance is a dominant character and could be succesful to obtain a model of control in areas where the transmission of schistosomiasis is only due to B. tenagophila (Coelho et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, different isolates of snail species can show a heterogeneous pattern to a parasite species infection (COELHO et al, 2004;ROSA et al, 2006;GARCIA et al, 2010;NACIF-PIMENTA et al, 2012).…”
Section: Introductionmentioning
confidence: 99%